Microbial communities show parallels at sites with distinct litter and soil characteristics - Sagova-Mareckova, Marketa; Omelka, Marek; Cermak, Ladislav; Kamenik, Zdenek; Olsovska, Jana; Hackl, Evelyn; Kopecky, Jan; Hadacek, Franz (Applied and environmental microbiology, 2011)
Plant and microbial community composition in connection with soil chemistry determines soil nutrient cycling. The study aimed at demonstrating links between plant and microbial communities and soil chemistry occurring among and within four sites: two pine forests with contrasting soil pH and two grasslands of dissimilar soil chemistry and vegetation. Soil was characterized by C and N content, particle size, and profiles of low-molecular-weight compounds determined by high-performance liquid chromatography (HPLC) of soil extracts. Bacterial and actinobacterial community composition was assessed by terminal restriction fragment length polymorphism (T-RFLP) and cloning followed by sequencing. Abundances of bacteria, fungi, and actinobacteria were determined by quantitative PCR. In addition, a pool of secondary metabolites was estimated by erm resistance genes coding for rRNA methyltransferases. The sites were characterized by a stable proportion of C/N within each site, while on a larger scale, the grasslands had a significantly lower C/N ratio than the forests. A Spearman's test showed that soil pH was correlated with bacterial community composition not only among sites but also within each site. Bacterial, actinobacterial, and fungal abundances were related to carbon sources while T-RFLP-assessed microbial community composition was correlated with the chemical environment represented by HPLC profiles. Actinobacteria community composition was the only studied microbial characteristic correlated to all measured factors. It was concluded that the microbial communities of our sites were influenced primarily not only by soil abiotic characteristics but also by dominant litter quality, particularly, by percentage of recalcitrant compounds.
Keywords: polymorfismus délky restrikčních fragmentů; shluková analýza; Hydrogen-Ion Concentration; Bacteria; rostliny; Methyltransferases; uhlík; DNA bakterií; Colony Count, Microbial; Carbon; Soil; Cluster Analysis; Nitrogen; Chromatography, High Pressure Liquid; dusík; fylogeneze; DNA, Bacterial; počet mikrobiálních kolonií; Plants; houby; Polymorphism, Restriction Fragment Length; Sequence Analysis, DNA; biodiverzita; vysokoúčinná kapalinová chromatografie; půdní mikrobiologie; Bacterial Load; sekvenční analýza DNA; Soil Microbiology; Fungi; Organic Chemicals; molekulární sekvence - údaje; methyltransferasy; koncentrace vodíkových iontů; Molecular Sequence Data; organické látky; půda; bakteriální nálož; Phylogeny; Biodiversity